High Temperature Synthesis and Characterization of Hydroxyapatite Doped with Silver Nanoparticles - SADJADI*, M.S.; EBRAHIMI AFARANI, H.R.; ZARE†, K. (Asian Journal of Chemistry, 2024)
Calcium hydroxyapatite, is a material which is closely resembles with bone apatite and exhibits excellent osteoconductivity. In this work, the synthesis of hydroxyapatite in a modified synthetic body fluid (SBF) solutions at 37 °C and pH of 7.4 was performed using novel chemical precipitation technique. Then after heat operation at 1200 ºC, on filtered precipitated result calcium hydroxyapatite were produced. Hydroxyapatite doped with silver nanoparticles was prepared by treatment with AgNO3 solution and reduction of Ag+ ions by sodium borohydrate solution. The formations of the silver nanoparticles on the calcium hydroxyapatite structure were confirmed by X-ray diffraction and transmission electron microscopy. Transmission electron microscopy image shows the nanostructure of silver particles, being formed on hydroxyapatite texture.